2011
DOI: 10.1182/blood-2011-01-328567
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between NOTCH and AKT signaling during murine megakaryocyte lineage specification

Abstract: The NOTCH signaling pathway is implicated in a broad range of developmental processes, including cell fate decisions. However, the molecular basis for its role at the different steps of stem cell lineage commitment is unclear. We recently identified the NOTCH signaling pathway as a positive regulator of megakaryocyte lineage specification during hematopoiesis, but the developmental pathways that allow hematopoietic stem cell differentiation into the erythro-megakaryocytic lineages remain controversial. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 50 publications
4
52
0
Order By: Relevance
“…25 Hence, even when embryonic development is not affected by the PTENa MO, megakaryopoiesis and thrombocyte formation depend on Pear1, at least in part, via the regulation of Ptena. Recent studies in MKs 22 and in thymocytes 23 have revealed that Hes1 is a negative regulator of Pten expression. We presently found evidence of HES1 upregulation in the PEAR1 knockdown in CD34 1 cells, but not in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…25 Hence, even when embryonic development is not affected by the PTENa MO, megakaryopoiesis and thrombocyte formation depend on Pear1, at least in part, via the regulation of Ptena. Recent studies in MKs 22 and in thymocytes 23 have revealed that Hes1 is a negative regulator of Pten expression. We presently found evidence of HES1 upregulation in the PEAR1 knockdown in CD34 1 cells, but not in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in this Drosophila model tissue suggests that chromatin modifications may accompany the Notch-regulated mitosis-to-endoreplication switch (Domanitskaya and Schüpbach, 2012). The involvement of Notch in regulating endoreplication appears conserved, as mammalian megakaryocyte differentiation is regulated in part by Notch, although the nature of this regulation (positive versus negative) may differ between humans and mice (Cornejo et al, 2011;Mercher et al, 2008;Poirault-Chassac et al, 2010).…”
Section: Regulation Of the Mitosis-to-endoreplication Switchmentioning
confidence: 99%
“…While the importance of NOTCH1 activity in T-cell development has been known for some time, [38][39][40] NOTCH has recently emerged to also function in myeloid, megakaryocyte and erythroid development. [41][42][43] Gain of NOTCH1 function is a hallmark of 50%-60% of children with T-ALL, 9,44 and is thought to function as an initiating event and a progression factor in T-ALL. [45][46][47] Therefore, one might have predicted that activating NOTCH1 mutations should have an unfavorable effect on treatment response and long-term outcome.…”
mentioning
confidence: 99%